Pengujian Kesamaan Profil ASN PPPK Kabupaten Bandung dan Kabupaten Sumedang Berdasarkan Gaji Pokok - Mufika Reviana Hidayat; Suwanda (Bandung Conference Series: Statistics, 2024)
Abstract. A Branch Office is a part of the Regional Government Unit responsible for managing governmental affairs in the fields of secondary education, maritime affairs and fisheries, energy and mineral resources, and forestry. It is established as a working unit of the department with a specific area of jurisdiction. The Branch Office of Education for Region VIII of West Java has duties that include the distribution of salaries and allowances for ASN teachers (civil servants) with the status of Government Employees with Employment Agreements (PPPK) in Bandung Regency and Sumedang Regency. The salary components consist of Basic Salary, General Allowance, Position Allowance, and Performance Allowance. The amount of the basic salary is stipulated in Presidential Regulation No. 98 of 2020, which is determined by rank and years of service. Therefore, the profile of ASN PPPK in the regencies/cities can be reflected in their basic salary. This paper compares the profile of ASN PPPK in Bandung Regency and Sumedang Regency based on a test of equality of the average or median basic salary. The research results show that the data does not come from a normal distribution at a 5% significance level. Using the Mann-Whitney Test at a 5% significance level, it can be concluded that the median basic salary of ASN PPPK between Bandung Regency and Sumedang Regency is not significantly different. Abstrak. Cabang Dinas adalah bagian dari Perangkat Daerah yang bertanggung jawab atas penyelenggaraan Urusan Pemerintahan di bidang pendidikan menengah, kelautan dan perikanan, energi dan sumber daya mineral, serta kehutanan, yang dibentuk sebagai unit kerja dinas dengan wilayah kerja tertentu. Kantor Cabang Dinas Pendidikan Wilayah VIII Jawa Barat memiliki tugas antara lain penyaluran gaji dan tunjangan bagi Guru ASN berstatus Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) di Kabupaten Bandung dan Kabupaten Sumedang. Komponen Gaji terdiri dari Gaji Pokok, Tunjangan Umum, Tunjangan Jabatan dan Tunjangan Kinerja. Besarnya gaji pokok tertuang dalam Perpres Nomor 98 Tahun 2020 yang ditentukan oleh golongan dan masa kerja. Oleh karena itu, profil ASN PPPK di kabupaten/kota dapat dilihat pada gajih pokoknya. Dalam makalah ini dilakukan perbandingan profil ASN PPPK di Kab. Bandung dan Kab. Sumedang berdasarkan pada pengujian kesamaan rata-rata atau median gajih pokok. Hasil Penelitian menunjukkan bahwa data bukan berasal dari distribusi normal pada taraf nyata 5%. Dengan menggunakan Uji Mann Whitney pada taraf nyata 5% dapat disimpulkan bahwa median gaji pokok ASN PPPK antara Kab. Bandung dan Kab. Sumedang tidak berbeda secara signifikan.